2017
DOI: 10.1080/14787210.2017.1320220
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to guidelines for the prescribing of antibiotics in acute infections at Namibia’s national referral hospital: a pilot study and the implications

Abstract: Compliance with NSTGs is suboptimal. Prescribing of combination antibiotics, penicillins and diagnosis of oral dental, genitourinary and ear, nose and throat infections were important predictors for NSTG compliance. There is a need to implement antibiotic indicators and stewardship programmes, and ensure access to NSTGs, to improve future antibiotic prescribing in Namibia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 52 publications
0
62
1
Order By: Relevance
“…For instance, 46% of antibiotic prescriptions in a recent study were not indicated by the guidelines . However, higher adherence rates were recently seen in Namibia (62%), although below national target rates of 95% . Guideline adherence is influenced by several factors including the level of training of PHC personnel, available resources at healthcare facilities, workload, staff motivation, staff experience and the availability of managerial tools for monitoring prescribing patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, 46% of antibiotic prescriptions in a recent study were not indicated by the guidelines . However, higher adherence rates were recently seen in Namibia (62%), although below national target rates of 95% . Guideline adherence is influenced by several factors including the level of training of PHC personnel, available resources at healthcare facilities, workload, staff motivation, staff experience and the availability of managerial tools for monitoring prescribing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…To address the irrational use of medicines, including inappropriate use of antibiotics leading to increasing rates of antimicrobial resistance (AMR) with its associated impact on morbidity, mortality and costs, the WHO in collaboration with the International Network for Rational Use of Drugs (INRUD) has developed core indicators for prescribing practices, patient care and facility‐specific factors . These include the number of antibiotics per prescription without looking at issues of necessity or whether prescribing adheres to current guidelines . The current WHO reference value for the average number of medicines per encounter is <2, with a comprehensive review between 1990 and 2009 reporting the average number among 104 countries was 2.6 for the Africa region .…”
Section: Introductionmentioning
confidence: 99%
“…Specific QIs also include adherence to guidelines. Adherence to guidelines has been found to better represent the quality of prescribing in ambulatory care versus current WHO/INRUD criteria 271,313,335,348 . However, it is important that there is only one national reference guideline since where multiple guidelines exist contradictions can occur 236 .…”
Section: Quality Indicators (Qis) To Improve Antibiotic Prescribing Imentioning
confidence: 99%
“…Half of the respondents stated that therapeutic interchange policies were the responsibility of PTCs, with PTCs generally considered the most ideal setting for such programmes, which is encouraging as they can ensure that any guidelines are based on scientific evidence and any national Essential Medicine List [17,[37][38][39]. Several actions were reported as part of the pharmacist's practice during substitution (Table 5) including communication with other health professionals and providing information on available alternatives.…”
Section: Discussionmentioning
confidence: 99%